Residential green space associated with the use of attention deficit hyperactivity disorder medication among Dutch children - de Vries, Sjerp; Verheij, Robert (Frontiers in Psychology, 2022)
Several studies have observed an inverse relationship between ADHD-related behavior of children, as reported by parents or teachers, and the amount of green space in their residential environment. Research using other, more objective measures to determine ADHD-prevalence are scarce and could strengthen the evidence base considerably. In this study, it is investigated whether a similar beneficial association will be observed if the use of ADHD-related medication is selected as outcome measure. More specifically, registry data from a health insurance company on the reimbursement of ADHD-related medication in 2011 were available for 248 270 children between 5 and 12 years of age. Amounts of green space within 250m and 500m of the home address were calculated. Multilevel logistic regression analyses for the prevalence of use were conducted, including the following covariates: gender, age, urbanity of the neighborhood, neighborhood socioeconomic status, and percentage of people with a non-Western migration background in the neighborhood population. Results showed that the amount of green space was inversely related to the prevalence of use of ADHD-medication. Moreover, the relationship was strongest among children living in the least wealthy neighborhoods and virtually absent among those living in the wealthiest neighborhoods. Results also show that in less wealthy neighborhoods there is on average less green space available nearby: children that are likely to benefit most from nearby greenspace tend to have the least of it.